CD39+Foxp3+ regulatory T Cells suppress pathogenic Th17 cells and are impaired in multiple sclerosis. - Fletcher, Jean; Mills, Kingston; O'Farrelly, Cliona; Moran, Barry (My University, 2009)
Despite the fact that CD4+CD25+Foxp3+ regulatory T cells (Treg cells) play a central role in maintaining self-tolerance and that IL-17-producing CD4+ T cells (Th17 cells) are pathogenic in many autoimmune diseases, evidence to date has indicated that Th17 cells are resistant to suppression by human Foxp3+ Treg cells. It was recently demonstrated that CD39, an ectonucleotidase which hydrolyses ATP, is expressed on a subset of human natural Treg cells. We found that although both CD4+CD25hiCD39+ and CD4+CD25hiCD39- T cells suppressed proliferation and IFN-g production by responder T cells, only the CD4+CD25hiCD39+, which were predominantly FoxP3+, suppressed IL-17 production, whereas CD4+CD25hiCD39- T cells produced IL-17. An examination of T cells from multiple sclerosis (MS) patients revealed a normal frequency of CD4+CD25+CD127loFoxP3+, but interestingly a deficit in the relative frequency and the suppressive function of CD4+CD25+CD127loFoxP3+CD39+ Treg cells. The mechanism of suppression by CD39+ Treg cells appears to require cell contact and can be duplicated by adenosine, which is produced from ATP by the ectonucleotidases CD39 and CD73. Our findings suggest that CD4+CD25+Foxp3+CD39+ Treg cells play an important role in constraining pathogenic Th17 cells and their reduction in MS patients might lead to an inability to control IL-17 mediated autoimmune inflammation.
PUBLISHED
Keywords: Immunology; T cells (Treg cells); CD39+Foxp3+; Immunology, Inflammation & Infection; Neuroscience